Science at the frontier (National Academy Press, 1992)
Contents: This book represents such a gathering. The authors report on the intellectual sparks that occurred when a group of the nation's brightest and most accomplished younger researchers gathered for a rare cross-disciplinary symposium covering the spectrum of science.